New school culture in the attitudes towards information and communication technology of the students of vocational schools in Osijek-Baranja County - Markulak, Vlasta (Array, 2021)
The development of technology over the last decade has fundamentally changed our daily lives, and consequently the methodological and didactic approach to the teaching process. The intensive development of information and communication technologies has introduced significant changes in the teaching processes in recent decades and focuses teaching methodology on issues of approaching e-learning and changes in teaching and learning to adapt teaching to the present requirements and opportunities. To satisfy the requirements of the contemporary school, culture can be interpreted as "historical creation (of the people) expressed through material and spiritual achievements, production, styles and ways of working – to put it simply a kind of wisdom of living" (Previšić, 2010, p. 170). This is exactly what the application of modern information and communication technologies offers for teaching and learning the English language as a foreign language. One of the important segments of the culture of the contemporary school is the teaching process, which must first of all be modern and innovative. The research aimed to examine the attitudes of the students of the vocational schools in Osijek-Baranja County towards information and communication technology in learning and teaching. The data were collected through a questionnaire and it was found that respondents are very positive about the use of information and communication technologies in learning and teaching, but they are also aware of some of the pitfalls that technology brings.